Higher evening metabolic responses contribute to diurnal variation of self-paced cycling performance - Wajdi Souissi; Omar Hammouda; Achraf Ammar; Mohamed Ayachi; Yasmine Bardiaa; Omayma Daoud; Imen Ben Hassen; Mohamed Souissi; Tarak Driss (Termedia Publishing House, 2021)
This study examined the effect of time of day (TOD) on physical performance, and physiological and perceptual responses to a 10-km cycling time trial (TT10km). Twelve physically trained subjects (20.3 ± 1.2 years, 74.3 ± 7.4 kg, 179.7 ± 5.5 cm) completed, in a randomized order, a TT10km in the morning and in the evening. Intra-aural temperature (IAT) was measured at rest and following the TT10km. Completion time, power output (PO), rating of perceived exertion (RPE), heart rate (HR), minute ventilation (V̇ E), oxygen uptake (V̇ O2), carbon dioxide production (V̇ CO2) and respiratory exchange ratio (RER) were assessed every km during the TT10km. Blood lactate concentration [La] and blood glucose concentration [Glu] were assessed before, during and immediately after the TT10km. Faster completion time (Δ = 15.0s, p = 0.03) and higher IAT (Δ = 0.33°C, p = 0.02 for pre-TT10km) were obtained in the evening compared to the morning with a significant correlation between Δ completion time and Δ IAT at post-TT10 km (r = -0.83, p = 0.04). V̇ O2, [La] and [Glu] increased significantly during both test sessions (p < 0.001) with higher values in the evening compared to the morning (p = 0.015, p = 0.04, p = 0.01, respectively). However, the remaining parameters were found to be only affected by the TT10km (p < 0.001). The TT10km generates a higher V̇ O2 and higher [La] and [Glu] responses, contributing to a better cycling performance in the evening compared to the morning. The similar magnitude of the TOD effect on completion time and IAT at post-TT10km confirms that core temperature is one of the underlying factors contributing to the diurnal variation in physical performance.